2019
DOI: 10.1177/2309499019878258
|View full text |Cite
|
Sign up to set email alerts
|

A potential need for surgeon consensus: Cementation techniques for total knee arthroplasty in orthopedic implant manufacturers’ guidelines lack consistency

Abstract: Aim: Given recent concerns regarding the influence of different cements and implants on the rate of aseptic failures in total knee arthroplasty (TKA), we wondered if cementation technique could play a role. The primary aim of this review was to collect and compare the surgeon education materials from eight orthopedic implant manufacturers to evaluate the manufacturers’ recommended cementation technique in TKA and identify if there was any consistency in these readily available guides as to the best practices o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Another finding of this study was the increased penetration around the stem of the implant when the osteotome technique was employed. Previous authors describe a <1% rate of loosening when employing this technique [32]. This difference existed when compared with both gun and layered techniques and persisted with both early and late cementation.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Another finding of this study was the increased penetration around the stem of the implant when the osteotome technique was employed. Previous authors describe a <1% rate of loosening when employing this technique [32]. This difference existed when compared with both gun and layered techniques and persisted with both early and late cementation.…”
Section: Discussionmentioning
confidence: 84%
“…This difference existed when compared with both gun and layered techniques and persisted with both early and late cementation. Again, some authors contend that cementation of the stem provides no benefit in resisting micromotion if penetration beneath the implant is adequate at 3-5 mm [30,32,33]. Furthermore, arguments have been made that full cementation may result in greater bone loss at revision and cause stress shielding.…”
Section: Discussionmentioning
confidence: 99%
“…The main limitation of this study was the retrospective design and that analyses were naturally limited to the data collected by the LROI, although all data were prospectively collected with a 96% completion rate of all arthroplasties performed in the Netherlands [26]. Furthermore, all cemented TKA were analysed as one group, while the manner of cementation varies between orthopaedic surgeons [13] as well as manufacture educational material [21]. However, as the effect of the manner of cementation and incidence of BCIS had not been determined to our best knowledge, it was justified to analyse the cemented prostheses as one group.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding cement application, however, there is some disagreement about the best approach. 11 - 13 Refsum et al 14 showed that in six out of ten cases, cement application was performed with a cement gun, and in four cases by finger-packing technique. The question of cement application to the undersurface of the prosthesis with or without cementation of the stem is still controversial.…”
Section: Introductionmentioning
confidence: 99%